Unusual MR Imaging Features in CT Hyperdense Posterior Fossa Dermoids: Report of Two Cases - Anbazhagan Sathiaprabhu; Nichanametla Sravani; Krishnan Nagarajan; Sekar Sabarish; Kapil Patil (Indian Journal of Neurosurgery)
Dermoids, either intracranial or in the rest of the body, usually have typical imaging findings due to their fat contents as fat density in computed tomography (CT) and T1- and T2-hyperintensity in magnetic resonance imaging (MRI). Variable imaging appearances have been described due to soft tissue contents, hair, calcification, or even tooth. Posterior fossa dermoids have been reported as a specific variant that shows hyperdensity in CT and mixed signal intensity in MRI. We report two cases of posterior fossa CT hyperdense dermoids that showed unusual MRI features in the form of signal loss in magnetization transfer images and lipid peak in magnetic resonance spectroscopy. Both patients underwent surgical resection and histopathological confirmation and the causes of this unusual imaging appearance are discussed.